The Universal Human Right to Marry and to Found a Family The Yogyakarta Principles and International Trends against LGBTQ Discrimination in the Fight for Marriage Equality (Philippine Law Journal, 2014)
The right to marry is among the major struggles of the Lesbian, Gay, Bisexual, Transgender and Queer ("LGBTQ") people. For the Filipino LGBTQ, it is a right deserved, which remains elusive in a jurisdiction where it is impliedly prohibited by the Constitution and the Family Code. Luckily, the sporadic movement of human rights worldwide has slowly begun to perforate the steel walls of oppressive heteronormative practices, structures and institutions. In light of the developing global trend which liberally views LGBTQ marriage, and particularly, the emergence of the 2008 Yogyakarta Principles as soft law, there is reason to hope for the emergence of a human rights framework that would allow us to properly address the issue of LGBTQ marriage in the Philippines.